Current strategies for treatment of intervertebral disc degeneration: substitution and regeneration possibilities - van Uden, Sebastião (2017)
Background: Intervertebral disc degeneration has an annual worldwide socioeconomic impact masked as low back pain of over 70 billion euros. This disease has a high prevalence over the working age class, which raises the socioeconomic impact over the years. Acute physical trauma or prolonged intervertebral disc mistreatment triggers a biochemical negative tendency of catabolic-anabolic balance that progress to a chronic degeneration disease. Current biomedical treatments are not only ineffective in the long-run, but can also cause degeneration to spread to adjacent intervertebral discs. Regenerative strategies are desperately needed in the clinics, such as: minimal invasive nucleus pulposus or annulus fibrosus treatments, total disc replacement, and cartilaginous endplates decalcification. Main Body: Herein, it is reviewed the state-of-the-art of intervertebral disc regeneration strategies from the perspective of cells, scaffolds, or constructs, including both popular and unique tissue engineering approaches. The premises for cell type and origin selection or even absence of cells is being explored. Choice of several raw materials and scaffold fabrication methods are evaluated. Extensive studies have been developed for fully regeneration of the annulus fibrosus and nucleus pulposus, together or separately, with a long set of different rationales already reported. Recent works show promising biomaterials and processing methods applied to intervertebral disc substitutive or regenerative strategies. Facing the abundance of studies presented in the literature aiming intervertebral disc regeneration it is interesting to observe how cartilaginous endplates have been extensively neglected, being this a major source of nutrients and water supply for the whole disc. Conclusion: Severalinnovative avenues for tackling intervertebral disc degeneration are being reported â from acellular to cellular approaches, but the cartilaginous endplates regeneration strategies remain unaddressed. Interestingly, patient-specific approaches show great promise in respecting patient anatomy and thus allow quicker translation to the clinics in the near future.